Juridical Analysis of Simultaneous Election Postpones during the COVID-19 Pandemic: Legal Certainty Perspective - Jauhar Nashrullah; Catur Wido Haruni; Sholahuddin Al-Fatih; Sayed Khalid Shahzad (Universitas Muhammadiyah Malang, 2022)
The COVID-19 pandemic has implications for the postponement of the Simultaneous Pilkades in Indonesia. It's interesting to examine more deeply how the Simultaneous Pilkades policy arrangements during the COVID-19 Pandemic are viewed from the aspect of legal certainty and the legal consequences of postponing the Pilkades during the COVID-19 Pandemic. The research method uses a normative juridical approach with the statute approach and case approach. Legal materials (primary, secondary ,tertiary) were collected through literature study and analyzed in depth using content analysis. Research shows that prior to the pandemic in the laws and regulations the rules regarding the postponement of Simultaneous Pilkades due to force majeure had not been regulated. The authority of the Ministry of Home Affairs to determine the postponement of the Simultaneous Pilkades also has multiple interpretations. The government's policy of issuing the Mendagri Circular is also inaccurate and does not provide legal certainty, the circular is not classified as a statutory regulation. The presence of Permendagri No.72 of 2020 provides legal certainty, the substance clearly regulates the authority of the Regent/Mayor to postpone the Simultaneous Pilkades. The legal consequence of postponing the Pilkades during the Pandemic Period is that many villages will be led by an Acting Village Head. In the future, the provisions regarding the postponement of Simultaneous Village Head Elections due to force majeure are clearly regulated in the legislation and in carrying out tasks by the Acting Village Head must be carried out with full responsibility, because the Acting has the same duties, authorities, obligations and rights as the definitive Village Head. Abstrak Pandemi COVID-19 berimplikasi pada penundaan Pilkades Serentak di Indonesia. Namun pengaturan ihwal penundaan Pilkades Serentak dalam peraturan perundang-undangan ternyata kurang jelas. Menarik untuk mengkaji lebih dalam bagaimana pengaturan kebijakan Pilkades Serentak di masa Pandemi COVID-19 ditinjau dari aspek kepastian hukum dan akibat hukum dari adanya penundaan Pilkades di masa Pandemi COVID-19. Metode penelitian menggunakan yuridis normatif dengan pendekatan perundang-undangan dan pendekatan kasus. Bahan-bahan hukum (primer, sekunder, tersier) dikumpulkan melalui studi kepustakaan dan dianalisa secara mendalam menggunakan metode analisis konten. Penelitian menunjukan bahwa sebelum pandemi dalam peraturan perundang-undangan (UU, PP, Permendagri) aturan mengenai penundaan Pilkades Serentak karena force majeur (bencana non alam) belum diatur. Kewenangan Kemendagri menetapkan penundaan Pilkades Serentak juga multitafsir. Kebijakan pemerintah mengeluarkan Surat Edaran Menteri Dalam Negeri juga kurang tepat dan tidak memberikan kepastian hukum, surat edaran bukan dikelompokkan sebagai sebuah peraturan perundang-undangan. Akhirnya kehadiran Permendagri No. 72 Tahun 2020 memberikan kepastian hukum, subtansinya mengatur secara jelas kewenangan Bupati/Walikota menunda Pilkades Serentak karena situasi darurat COVID-19 serta mekanisme dan teknis pelaksanaan Pilkades Serentak dalam situasi darurat COVID-19. Akibat hukum dari penundaan Pilkades di Masa Pandemi adalah banyak desa yang akan dipimpin oleh seorang Penjabat Kepala Desa. Kedepan ketentuan mengenai penundaan Pilkades Serentak karena force majeur diatur secara jelas dalam peraturan perundangan-undangan dan dalam pelaksanaan tugas oleh Penjabat Kepala Desa harus dilakukan dengan penuh tanggung jawab, karena Penjabat memiliki tugas, wewenang, kewajiban dan hak yang sama seperti Kepala Desa definitif.